(untitled) (Journal of Social Sciences Review, 2023)
This study focuses on exploring the causes and consequences of child labour on children’s health among Afghan’s refugees living in Peshawar. Data were collected from 100 child labour respondents through in-depth interviews from an area of research, and results were drawn through analysis to reach a conclusion. This study found that these child labour respondents have body aches, headaches and joint pain, skin disease, eye problems, coughing, and tiredness, are affected by large family size, facing harassment at the workplace that torcher them physically and mentally as there is no such mechanism that can cure their illness or address their harassment issue. Long working hours, less rest, and heavy loads affect their health negatively. Due to a lack of money and time, these children cannot visit doctors. Even if a doctor’s check is free of cost, they do not purchase medicine. These children often rely upon homemade medicine, which is offered by their families. Therefore, this study found that health issues among child labour respondents are a common phenomenon, and treatment issues need to be resolved for their health and their future.